Pulse oxygen saturation and neurologic assessment in human neonates after vaginal and cesarean delivery - Gonzales G.F. (1998)
This study was supported in part by a Maintenance Grant from the World Health Organization, Special Programme of Research, Development and Research Training in Human Reproduction, and by a grant from the Consejo Nacional de Ciencia y Tecnologıa CONCYTEC , Peru.